Coconut Micropropagation in Mexico using Plumule and Floral Explants - Oropeza, Carlos; Sáenz, Luis; Chan, José Luis; Sandoval, Gabriela; Pérez-Núñez, Teresa; Narvaez, Maria; Rodríguez, Guillermo; Borroto, Carlos (International Coconut Community Journal, 2016)
This paper focuses on the research efforts carried out by CICY in Mexico on micropropagation of coconut. They started during the nineties in collaboration with Wye College (UK) and ORSTOM-CIRAD (France), with the development of a protocol that was reproducible and more efficient than previous ones, based on plumule explants grown in different media based on Y3 medium added with activated charcoal, gelling agent and of particular importance growth regulators 2,4-dichlorophenoxyacetic acid (2,4-D) and 6-benzylaminopurine (BAP). Within the next decade basic research was carried out to study the process of somatic embryogenesis from plumule explants, with an approach including morpho-histological, physiological, biochemical and molecular points of view, in order to gain knowledge that could be useful to further improvement of the process. Also different practical approaches were tested including changes in the media formulation, embryogenic callus multiplication and secondary somatic embryogenesis. As a result a highly efficient protocol was developed that could potentially yield over a hundred thousand somatic embryos from a single plumule explant. Embryos were able to germinate and convert to plantlets, that after planting, successfully grew to sexual maturity and fruit production. This protocol is currently being scaled up to a semi-commercial level. Also within the past five years, a protocol using rachilla explants has been developed for the production of embryogenic callus and its multiplication, and embryos produced were able to germinate and convert to plantlets, setting the basis to develop a process for massive propagation of coconut, such as the one already developed using plumule explants.